A novel double-layer active equalization scheme for lithium-ion batteries combining wireless power transfer - Liu, Xinghua (2024)
Battery packs inconsistency is inevitable in the use of series-connected cells. For packs equalization in confined environments, direct electrical contact is unpermitted. To address this issue, a novel double-layer equalization topology is proposed. It combines a wireless equalizer for inter-group equalization with a wired active equalizer for intra-group equalization. Firstly, current and voltage of intra-group equalization and inter-group equalization are introduced. Then, the Thevenin equivalent model is developed and parameter identification of the model is performed using the least squares method with a forgetting factor. In addition, the intra-group equalization parameters and inter-group equalization parameters are designed to improve the equalization performance. For different currents corresponding to different cell resistances, the duty cycle of the buck circuit is analyzed to achieve a constant equalization current. The optimal switching frequency and equalization method for intra-group equalization are designed to improve the equalization effect. Finally, an equalization experiment with eight cells is designed to validate the effectiveness of the proposed topology and strategy. The experimental results demonstrate that the designed topology has better equalization performance under different initial SOC distributions and switching frequencies. It verifies that the equilibrium model is able to effectively solve the inconsistency of the series-connected battery packs.